Climatic influences on the Paleogene evolution of alkenones. (28th March 2014) - Brassell, Simon C.
Abstract Application of the alkenone paleotemperature proxy (UK'37) for marine sediments is typically constrained by three factors: (i) an absence of alkatrienones in sediments deposited where ocean temperatures exceed 28°C, (ii) loss of alkenones in thermally altered sediments, and (iii) poor preservation of alkenone signals due to oxidative degradation. In addition, there appears to be a temporal limit on the occurrence of alkatrienones, which are conspicuously absent in all alkenone‐containing sediments from the early Aptian to the immediate aftermath of the Early Eocene Climatic Optimum (EECO) when they first appeared in Arctic Ocean sediments. Compilation of reported and previously unpublished alkenone distributions for the Paleogene coupled with assessment of co‐occurring calcareous nannoplankton genera within the Noelaerhabdaceae provide evidence that evolutionary developments in alkenone occurrences include biosynthetic responses likely triggered by climate change. The timing of emergence of alkatrienones post‐EECO and their subsequent appearance at all latitudes during the middle Eocene accompanies expansion of the calcareous nannoplankton genus Reticulofenestra coincident with significant climate‐driven changes in oceanic conditions, including (i) modification of trophic structure associated with weakened thermal stratification, (ii) higher productivity facilitated by enhanced nutrient influx, and (iii) changes in seasonality, initially at high latitudes, related to greater latitudinal temperature gradients. Collectively, these changes would serve to favor eurythermal/eurytrophic algae, like Reticulofenestra, with a biomechanism to store energy through production of lipid bodies rich in alkenones during episodes of higher nutrient availability. This ability likely enhanced the viability of this marine haptophyte when nutrients were limiting, ultimately ensuring its evolutionary success.